The main trends of integration of the Russian financial market into the world financial market (Путеводитель предпринимателя, 2020)
Increase of efficiency of the Russian financial market depends much on its complete integration into the world financial market. A number of laws deal with financial system of Russia have been passed recently and their aim is to speed up this process considerably to make it more dynamic. As a result, the Russianfinancial market infrastructure will have to become the part of the globalfinancial market infrastructure. No doubt, it will increase the investment attractiveness of the Russian economy.